Pertimbangan Hakim Terhadap Putusan Perceraian Akibat Kekerasan Psikis di Pengadilan Negeri Kelas I A Palangka Raya - Mulida Hayati; Aristoteles, Aristoteles; Evi, Evi; Angelica Rya (LPPM Universitas Ekasakti Padang, 2024)
Palangka Raya class IA state. Object of research on divorce lawsuits at the Palangka Raya Class IA District Court. The aim of the research is to find out whether psychological violence can be used as a reason for a divorce suit at the Class I A Palangka Raya District Court, and to find out the judge's consideration of the divorce decision due to psychological violence at the Class I A Palangka Raya District Court. The research uses qualitative methods with empirical field or juridical research. Psychological violence can be used as a reason for divorce in court because it is in accordance with the regulations contained in the Marriage Law, Domestic Violence Eradication Law and Compilation of Islamic Law, as well as looking at the benefits contained in the judge's decision. The reason the plaintiff filed the lawsuit was because of psychological violence which resulted in mental stress or feelings, but this was not used as the main reason for the judge to consider granting the plaintiff's lawsuit.